Theoretic – practical analysis of the detailed customs declaration - URSU, Viorica; STAMATI, Mihaela (Journal of Social Sciences, 2020)
Any of individuals or legal persons, regardless of the form of ownership, have the right to introduce into and out of the country goods and means of transport according to the legislation in force, but when crossing the border, they are subject to the declaration of the customs body. The declaration is considered the main stage of the procedure for completing the customs documents, which in turn is the component part of the customs activity. Once the goods or transports enter or leave the state border, they will be placed under a customs regime, and will be the subject of a customs declaration. This condition for declaring goods is regulated by the Customs Code of the Republic of Moldova. Thus, art. 173 stipulates that "goods and means of transport crossing the customs border, goods and means of transport whose customs destination changes, other goods and means of transport in the cases established under the law are declared to the customs body". According to the customs legislation, the declaration of the goods and their presentation for customs clearance is made by the declarants or their representatives, by submitting a detailed customs declaration, in writing, at the end of the transit procedure or within 20 days from the date of filing the summary declaration. Thus, this article will bring to the fore the definition and analysis of this type of customs declaration - the customs declaration in detail.